Effect of Biofortified and Non-Biofortified Varieties and Zinc Fertilization Strategies on Growth, Productivity and Profitability of Rice - Nayak, Somanath; Shivay, Yashbir Singh; Prasanna, Radha; Mandi, Sunil (International Journal of Bio-resource and Stress Management, 2022)
The field experiment was conducted in the rainy (Kharif, June to October) seasons of 2019 and 2020 at ICAR-Indian Agricultural Research Institute, New Delhi, India with the objective to appraise the effect of biofortified and non-biofortified varieties and zinc fertilization strategies on the growth, productivity and profitability of rice. The biofortified variety DRR Dhan 45 recorded a higher value of dry matter accumulation, leaf area index, and crop growth rate, and the non-biofortified variety Pusa 44 recorded higher effective tillers, panicle weight, filled grain weight per panicle, number of filled grains and total grains per panicle, fertility percentage and grain yield (5.2 t ha-1), though the performance of both varieties was statistically similar. But, the higher straw yield was recorded with the non-biofortified variety, Pusa Basmati 1121 (10.8 t ha-1). Pusa Basmati 1509 recorded higher cost of cultivation, gross returns, net returns and B:C. Among zinc fertilization strategies, soil application of 2.5 kg Zn ha-1 along with the foliar application of 0.5% ZnSO4.7H2O at maximum tillering and anthesis stages recorded higher growth parameters, yield, and yield attributes and better economics. On average, the soil+foliar Zn application increased grain yield by 14% and straw yield by 10.5%, and gross returns and net returns by 15.6% and 26.7%, respectively, than the control. Cultivation of rice varieties, Pusa 44 or DRR Dhan 45, along with soil+foliar Zn fertilization enhanced growth and productivity, while the aromatic variety, Pusa Basmati 1509 enhanced the profitability.